A PROSPECTIVE STUDY ON PREGNANCY COMPLICATED WITH JAUNDICE AND FETOMATERNAL OUTCOME - WARRIER, HARIDAS GOVINDA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to determine biochemical factors and maternofetal outcome in women with jaundice during pregnancy and to study its association with jaundice in pregnancy. Methods: It was an observational study done among 60 pregnant patients with abnormal liver functioning. Laboratory parameters were studied which mainly includes liver function tests. Demographics and the detailed clinical history were recorded. The detailed laboratory investigation was carried out to study the complications concerning biochemical parameter. SPSS (Version 22.0) was used for analysis. Results: HELLP syndrome was the most common etiology (45%). Decreased levels of hemoglobin observed in 75%, increased total leukocyte count observed in 26%, and low platelet count observed in 34%, respectively. Among mothers, most common adverse outcome was requirement of emergency lower segment cesarean section (45%). Maternal outcomes were significantly associated with raised direct bilirubin, raised serum glutamic pyruvic transaminase, raised alkaline phosphatase, and thrombocytopenia (p=0.03, p=0.01, p=0.02, and p=0.01, respectively). Conclusion: Hepatic dysfunction during pregnancy is associated with adverse events for both the mother and the fetus.